Delay to mental healthcare in a cohort of Canadian Armed Forces personnel with deployment-related mental disorders, 2002–2011: a retrospective cohort study. Issue 9 (8th September 2016) - Boulos, David; Zamorski, Mark A
Abstract : Objective: To assess whether the delay to care among Canadian Armed Forces (CAF) personnel who sought care for a mental disorder changed over time and in association with CAF mental health system augmentations. Design: A stratified, random sample (n=2014) was selected for study from an Afghanistan-deployed cohort (N=30 513) and the 415 (weighted N=4108) individuals diagnosed with an Afghanistan service-related mental disorder were further assessed. Diagnosis-related data were abstracted from medical records (22 June 2010 to 30 May 2011). Other data were extracted from administrative databases. Delay to care was assessed across five mental health system eras: 2002/2004, 2005/2006, 2007, 2008 and 2009/2010. Weighted Cox proportional hazards regression assessed the association between era, handled as a time-dependent covariate, and the outcome while controlling for a broad range of potential confounders (ie, sociodemographic, military and clinical characteristics). Taylor series linearisation methods and sample design weights were applied in generating descriptive and regression analysis statistics. Primary outcome: The outcome was the delay to mental healthcare, defined as the latency from most recent Afghanistan deployment return date to diagnosis date, among individuals with an Afghanistan service-related mental disorder diagnosis. Results: Mean delay to care was 551 days (95% CI 501 to 602); the median was 400 days. Delay to care decreased in subsequent eras relative to 2002/2004; however, only the most recent era (2009/2010) was statistically significant (adjusted HR (aHR): 3.01 (95% CI 1.91 to 4.73)). Men, operations support occupations, higher ranks, non-musculoskeletal comorbidities and fewer years of military service were also independently associated with longer delays to care. Conclusions: CAF mental health system changes were associated with reduced delays to mental healthcare. Further evaluation research is needed to identify the key system changes that were most impactful.